Diffuse and spot mode of cathode arc attachments in an atmospheric magnetically rotating argon arc. (25th January 2016) - Chen, Tang; Wang, Cheng; Liao, Meng-Ran; Xia, Wei-Dong
Abstract: A model including the cathode, near-cathode region, and arc column was constructed. Specifically, a thermal perturbation layer at the arc fringe was calculated in order to couple sheath/presheath modelling with typical arc column modelling. Comparative investigation of two modes of attachment of a dc (100, 150, 200 A) atmospheric-pressure arc in argon to a thermionic cathode made of pure tungsten was conducted. Computational data revealed that there exists two modes of arc discharge: the spot mode, which has an obvious cathode surface temperature peak in the arc attachment centre; and the diffuse mode, which has a flat cathode surface temperature distribution and a larger arc attachment area. The modelling results of the arc attachment agree with previous experimental observations for the diffuse mode. A further 3D simulation is obviously needed to investigate the non-axisymmetrical features, especially for the spot mode.